2023
DOI: 10.1002/advs.202302974
|View full text |Cite
|
Sign up to set email alerts
|

Highly Strain‐Stable Intrinsically Stretchable Olfactory Sensors for Imperceptible Health Monitoring

Guodong Zhao,
Jing Sun,
Mingxin Zhang
et al.

Abstract: Intrinsically stretchable gas sensors possess outstanding advantages in seamless conformability and high‐comfort wearability for real‐time detection toward skin/respiration gases, making them promising candidates for health monitoring and non‐invasive disease diagnosis and therapy. However, the strain‐induced deformation of the sensitive semiconductor layers possibly causes the sensing signal drift, resulting in failure in achievement of the reliable gas detection. Herein, a surprising result that the stretcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
6
0
3
Order By: Relevance
“…The rapid development of AI has raised higher requirements for the form of electronic products, with flexible wearable electronic devices becoming a focus of research. Flexible devices not only bring portability but are also crucial for biomedical applications such as physiological monitoring, implant therapy, electronic skin, and human–machine interfaces. ,, The synaptic device exhibits excellent electrical performance when the gate voltage equals zero after state aggregation, greatly improving the possibility of preparing and applying flexible synaptic devices, without considering the presence of the gate. To ensure the device’s conformability, PDMS is used as a support layer for the device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The rapid development of AI has raised higher requirements for the form of electronic products, with flexible wearable electronic devices becoming a focus of research. Flexible devices not only bring portability but are also crucial for biomedical applications such as physiological monitoring, implant therapy, electronic skin, and human–machine interfaces. ,, The synaptic device exhibits excellent electrical performance when the gate voltage equals zero after state aggregation, greatly improving the possibility of preparing and applying flexible synaptic devices, without considering the presence of the gate. To ensure the device’s conformability, PDMS is used as a support layer for the device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Tang et al addressed this need by preparing intrinsically stretchable FET-type gas sensors, employing IDTBT as the semiconductor layer, PDMS as the insulating layer, and PEDOT:PSS/SWCNT as the electrodes. 53 They found that the ultra-large molecular spacing of polymer semiconductors allowed gas molecules to diffuse, regardless of whether the semiconductor was stretched or not. Therefore, the stretchable polymer semiconductor had strain-insensitive gas-sensing properties.…”
Section: Applications Of Intrinsically Stretchable Ofetsmentioning
confidence: 99%
“…The rapid development of sensing technology provides important technical support for human beings to effectively monitor the surrounding physical space, greatly enhancing their ability to cope with various emergencies. Various types of sensors have shown great potential for development in the fields of industrial production, intelligent medical care, , human–computer interaction systems, as well as physiological signal perception and motion pattern recognition. Capacitive and piezoresistive sensors are the most commonly used in flexible pressure sensors. Both types of sensors have their unique advantages.…”
Section: Introductionmentioning
confidence: 99%